Essential role of lattice oxygen in methanol electrochemical refinery toward formate - Meng, Fanxu (2023)
Developing technologies based on the concept of methanol electrochemical refinery (e-refinery) is promising for carbon-neutral chemical manufacturing. However, a lack of mechanism understanding and material properties that control the methanol e-refinery catalytic performances hinders the discovery of efficient catalysts. Here, using 18O isotope-labeled catalysts, we find that the oxygen atoms in formate generated during the methanol e-refinery reaction can originate from the catalysts' lattice oxygen and the O-2p-band center levels can serve as an effective descriptor to predict the catalytic performance of the catalysts, namely, the formate production rates and Faradaic efficiencies. Moreover, the identified descriptor is consolidated by additional catalysts and theoretical mechanisms from density functional theory. This work provides direct experimental evidence of lattice oxygen participation and offers an efficient design principle for the methanol e-refinery reaction to formate, which may open up new research directions in understanding and designing electrified conversions of small molecules.